2022
DOI: 10.3390/jcm11102909
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNAs Acting as miRNAs’ Sponges and Their Roles in Stem Cells

Abstract: Circular RNAs (circRNAs), a novel type of endogenous RNAs, have become a subject of intensive research. It has been found that circRNAs are important players in cell differentiation and tissue homeostasis, as well as disease development. Moreover, the expression of circRNAs is usually not correlated with their parental gene expression, indicating that they are not only a steady-state by-product of mRNA splicing but a product of variable splicing under novel regulation. Sequence conservation analysis has also d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 137 publications
0
3
0
Order By: Relevance
“…Furthermore, MSC exosomes have demonstrated benefits in brain injury, accelerating recovery through neurosynaptic remodeling, neurogenesis, and angiogenesis[ 74 ]. Besides miRNAs, circRNAs are resistant to degradation, act as miRNA sponges in neural apoptosis, angiogenesis, and synaptic plasticity modulation, and hold immense promise for neuroregeneration[ 75 ]. MSC-derived exosomal lncRNAs have been reported to enhance neuronal survival and promote axonal regeneration after nerve injury.…”
Section: Cell-free Therapy-based Approaches For Pni Repairmentioning
confidence: 99%
“…Furthermore, MSC exosomes have demonstrated benefits in brain injury, accelerating recovery through neurosynaptic remodeling, neurogenesis, and angiogenesis[ 74 ]. Besides miRNAs, circRNAs are resistant to degradation, act as miRNA sponges in neural apoptosis, angiogenesis, and synaptic plasticity modulation, and hold immense promise for neuroregeneration[ 75 ]. MSC-derived exosomal lncRNAs have been reported to enhance neuronal survival and promote axonal regeneration after nerve injury.…”
Section: Cell-free Therapy-based Approaches For Pni Repairmentioning
confidence: 99%
“…An interesting question is hence, if TarPmiR is able to differentiate between circRNAs that are active miRNA sponges and those that have other functions. Previous research has defined three types of circular RNAs based on structural features -exonic circular (ecirc) RNAs, circular intronic RNA (ciRNA), and exon-intron circRNA (EIciRNA) [47][48][49]. It has been suggested that ecircRNAs function predominantly through a miRNA sponging effect in the cytoplasm whereas other circular RNA forms (e.g.…”
Section: A Cerna Network Reveals Circrnas Acting As Mirna Spongesmentioning
confidence: 99%
“…These attributes of circRNAs imply that they have unique biological functions rather than being a by-product of pre-mRNA processing. Over the last decade, many researchers have revealed that circRNAs can function as microRNA sponges, interact with RNA-binding proteins (RBPs), modulate alternative splicing and transcription, and even translate into polypeptides ( Patop et al, 2019 ; Huang et al, 2020 ; Xiao et al, 2022 ). Accumulating evidence indicates that circRNAs are involved in neurological disorders, including ischemic brain injury, Alzheimer’s disease, and PTSD ( Mo et al, 2020 ; Su et al, 2021 ; Du et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%